PEMBUATAN MANISAN KERING REBUNG DENGAN VARIASI KONSENTRASI GULA - Mutiara Izzah; Akhyar Ali; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of different sugar concentrations on the quality of candy dried shoot. This study used Completely Randomized Design with four treatments and four replications. The treatments used for candy dried shoot P1 (shoot immersion with sugar 40%), P2 (shoot immersion with sugar 50%), P3 (shoot immersion with sugar 60%), and P4 (shoot immersion with sugar70%). The obtained were analyzed statistically using Analysis of Variance and Duncan’s New Multiple Range Test at 5% level. The results showed that the sugar concentration had a significant effect on water content, ash content, sucrose content, and sensory assessment descriptively and hedonic. The selected treatments were P4 (70% sugar immersion with water content (18.37%), ash content (1.99%), sucrose content (48.14%), brownish white color, slightly scented shoot, tasty candy shoot, and the overall assessment of candy dried shoot favored by the panelists.Keywords: Candied dried, shoot, and sugar concentration.